Efeitos da suplementação de isoflavonas associadas ao treinamento com exercícios físicos combinados nos níveis lipídicos, marcadores inflamatórios e de estresse oxidativo em mulheres pósmenopausadas - Giolo, Jéssica Sanjulião (2018)
Introduction: Physical exercise or isoflavone consumption may improve the inflammatory state and oxidative stress, but the effect of the combination of these two interventions is not yet clear in the literature. Our hypothesis was that isoflavones may enhance the beneficial effects of exercise. Objective: This study tested the effect of isoflavone supplementation in addition to combined exercise training on plasma lipid levels, inflammatory markers and oxidative stress in postmenopausal women. Material and methods: Thirty-two healthy and non-obese postmenopausal women without hormone therapy were randomly assigned to exercise+placebo (EXE+PLA, n=15) or exercise+isoflavone supplementation (EXE+ISO, n=17) groups. They performed 30 sessions during ten weeks of combined exercises (aerobic plus resistance), and consumed 100 mg of isoflavone supplementation or placebo. Blood samples were collected after an overnight fast to analyze the lipid profile, interleukin-6, interleukin-8, superoxide dismutase (SOD), total antioxidant capacity (FRAP), and thiobarbituric acid reactive substances (TBARS) before and after ten weeks of the intervention. Results: There were no differences in the changes (pre vs post) between groups in any of the inflammatory markers, oxidative stress, or lipid profile variables. However, only EXE+PLA presented significant changes (p≤0.05) in total cholesterol (= -13.07 mg / dL), and interleukin-8 was different between pre and posttests (p<0.001) in both groups (= 7.61 and 5.61 pg / mL). Conclusion: The combination of isoflavone supplementation and exercise training did not alter oxidative stress markers in postmenopausal women, but this exercise training increase IL-8, and the isoflavone apparently blunts the exercise-induced effects on blood cholesterol levels.